2021
DOI: 10.3389/fpsyt.2020.611579
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Substance Use Behaviors With Suicidal Ideation and Suicide Attempts Among US and Chinese Adolescents

Abstract: Background: Adolescence has been described as a period of increased health risk-taking behaviors. Given the variety of cultural contexts, healthcare systems, and public health policies in different regions, the present study aimed to determine whether there are similar or different associations of substance use behaviors with suicidal ideation and suicide attempts among US and Chinese adolescents.Methods: This study included a total of 14,765 US adolescents from the 2017 National Youth Risk Behavior Surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
0
15
1
1
Order By: Relevance
“…In particular, three stages of suicidal behaviours were assessed with single items instead of dedicated interviews or psychometric instruments. Although the measurement of this study is practical and efficient in a large-size sample study (Guo et al ., 2021 ), we will adopt more rigorous assessment in future studies. Third, we only included two core subtypes of CM in the analysis, including neglect and physical abuse, while the direct and indirect influence of emotional abuse and sexual abuse on suicidal risk was ignored.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, three stages of suicidal behaviours were assessed with single items instead of dedicated interviews or psychometric instruments. Although the measurement of this study is practical and efficient in a large-size sample study (Guo et al ., 2021 ), we will adopt more rigorous assessment in future studies. Third, we only included two core subtypes of CM in the analysis, including neglect and physical abuse, while the direct and indirect influence of emotional abuse and sexual abuse on suicidal risk was ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol use is a direct threat to adolescent health, and it creates risks of around 230 different identified health outcomes in the form of disease, injury, or mental health problems [ 14 , 15 , 16 ]. Recent studies found that adolescence alcohol use is linked to suicidal ideation and suicide attempts [ 17 , 18 ], gambling, abnormal fear-related behavior, and alcohol use disorders [ 19 , 20 ]. Alcohol use and abuse among young people (under 21 years of age) is a pervasive problem worldwide [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use and abuse among young people (under 21 years of age) is a pervasive problem worldwide [ 21 ]. In China, alcohol drinking is more common than other substance use behavior among adolescents [ 18 ], given the fact that alcohol drinking is more culturally acceptable in China. Existing studies indicate that teenagers’ drinking behavior is becoming increasingly serious, and teenagers’ heavy drinking and drunken behavior has also increased.…”
Section: Introductionmentioning
confidence: 99%
“…In the suicidal process of adolescents, suicidal ideation has been considered one of the major factors causing the suicide of adolescents [ 8 , 12 ]. Through a survey of 24,345 Chinese adolescents, Guo et al found that 13.7% of adolescents experience suicidal ideation [ 13 ]. Therefore, society must pay more attention to the Chinese adolescent suicidal ideation problem [ 8 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through a survey of 24,345 Chinese adolescents, Guo et al found that 13.7% of adolescents experience suicidal ideation [ 13 ]. Therefore, society must pay more attention to the Chinese adolescent suicidal ideation problem [ 8 , 13 ]. Existing studies have revealed that risk factors such as an unsupportive family environment [ 2 ], drug abuse [ 14 ], and bullying may affect the suicidal ideation of adolescents, of which an unsupportive family environment plays a crucial role in its formation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%